MANAGEMENT STRUCTURES OF CHILDREN'S MUSIC AND ART SCHOOLS - Sharipov Sherzod Maqsud ugli (Journals Park Publishing, 2024)
The article examines the management competencies of the leading personnel of children's music and art schools. The management mechanism and procedure of children's music and art schools are reflected.
Keywords: music direction, art direction, concertmaster, pedagogical council, instrument, children's music and art school.